Energy efficiency, rebound effect and environmental tax reform in Indonesia. (5th February 2020) - Sobri, Arif Rahman; Hartono, Djoni; Lestari, Nina Indriati
Energy intensity level in Indonesia is decreasing, which is a sign of energy efficiency improvement. However, with the presence of rebound effect, energy consumption becomes challenging to reduce. With a general equilibrium (CGE) model application, this study analyses a rebound effect existence in Indonesia and whether the energy subsidy and income tax reduction could lessen the rebound effect. While it confirms the rebound effect presence, energy subsidy reduction policy could play an important part in determining its level. The policy is believed to reduce rebound effect on fuel oil while elevates it when it comes to electricity and gas. Furthermore, it leads to a positive effect on the economy. However, the other policy such as income tax reduction, indicates contrarily.